Sosialisasi Ketahanan Ekonomi Melalui Pemberdayaan BUMDes Kepada Siswa SMK Di Bandar Lampung - Kusumawardani, Niken (ANDASIH Jurnal Pengabdian kepada Masyarakat, 2024)
Abstract Economic resilience is one of the important pillars in village development. Villages with strong economic resilience will be able to face various crises and global economic changes. One strategy to increase village economic resilience is to empower the Village Owned Enterprises (BUMDes). This study aims to improve the knowledge and understanding of students of SMKN 1 Bandar Lampung about economic resilience and the role of BUMDes in improving community welfare. The method used in this research is lectures, discussions, and question and answer sessions. The results of the study show that students of SMKN 1 Bandar Lampung have better knowledge and understanding of economic resilience and the role of BUMDes in improving community welfare. Students are also motivated to participate in empowering BUMDes in their villages. Â Keywords : Economic Resilience, BUMDes, Empowerment, Students of Vocational School